Defining the role of TRPM4 in broadly responsive taste receptor cells - Dutta Banik, Debarghya; Medler, Kathryn F. (Frontiers in Cellular Neuroscience, 2023)
Peripheral taste receptor cells use multiple signaling pathways to transduce taste stimuli into output signals that are sent to the brain. We have previously identified a subpopulation of Type III taste cells that are broadly responsive (BR) and respond to multiple taste stimuli including bitter, sweet, umami, and sour. These BR cells use a PLCbeta3/IP3R1 signaling pathway to detect bitter, sweet, and umami stimuli and use a separate pathway to detect sour. Currently, the downstream targets of the PLCbeta3 signaling pathway are unknown. Here we identify TRPM4, a monovalent selective TRP channel, as an important downstream component in this signaling pathway. Using live cell imaging on isolated taste receptor cells from mice, we show that inhibition of TRPM4 abolished the taste-evoked sodium responses and significantly reduced the taste-evoked calcium responses in BR cells. Since BR cells are a subpopulation of Type III taste cells, they have conventional chemical synapses that require the activation of voltage-gated calcium channels (VGCCs) to cause neurotransmitter release. We found that TRPM4-dependent membrane depolarization selectively activates L-type VGCCs in these cells. The calcium influx through L-type VGCCs also generates a calcium-induced calcium release (CICR) via ryanodine receptors that enhances TRPM4 activity. Together these signaling events amplify the initial taste response to generate an appropriate output signal.